توظيف التراث في شعر ابن الدمينة - قاسم غباش, وصال (Journal of College of Education, 2019)
Heritage represeent s  stok It preserres its identity and belonging heritage is the source of inspiration poets affect them, and many of them rcsort  to this heritage vnhlon it and employ it their poetry, and the poet Ibn al-Damianah one  of these poets, an Islamic poet of the poets spinning virgin could employ the Arab heritage in his poetry .The title of the research(The exploitation of heritage in the poetry of Ibn al-Damianah).And the section of the search to the entrance talked about the and his life and age and poetry, and dealt with the first section of religious heritage, The second to picws devoted to literary heritage and proverbs, The third topic was to talk about the his torical heritage , then the conclusion of the research and its results, and a list of sources and references.